New Taxa of Family Xylariaceae from Arunachal Pradesh - Deb, Sourabh; Tali, Aguti; Singh, R. K. (Indian Forester, 2008)
Different parts of Arunachal Pradesh were surveyed to collect three genera Xylaria, Daldinia and Hypoxylon of the family Xylariaceae. A total of 10 species belonging to these genera were identified, which included eight species of Xylaria and one species each of Daldinia and Hypoxylon and are the first report from the state.